Penerapan Blockchain dalam Manajemen Data Akademik - Green, Thomas; Chakim, Heru Riza; Andayani, Dwi; Rusilowati, Umi (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
The rapid development of digital technologies has led to significant transformations in higher education management, particularly in academic data handling. The traditional methods of managing academic records are often prone to issues related to security, transparency, and efficiency. This research explores the application of blockchain technology as a solution for managing academic data securely and transparently. A qualitative approach was used, involving case studies of universities that have implemented blockchain in their data management systems. Data were gathered through interviews with key stakeholders, including administrators and IT specialists, to understand the effectiveness of blockchain integration in ensuring data integrity. The findings indicate that blockchain technology provides a decentralized and immutable ledger, significantly enhancing data security, reducing fraud, and improving the authenticity of academic credentials. Moreover, it streamlines the verification process, making it more efficient and reliable. The integration of blockchain into academic data management systems can address the prevalent issues in traditional record-keeping systems by offering a secure, transparent, and efficient method for handling academic data. This study highlights the potential of blockchain to revolutionize higher education management, offering long-term benefits in terms of privacy, transparency, and decision-making efficiency.